THE ENDOSCOPIC TRANSNASAL (ENDONASAL) APPROACH IN NEUROSURGERY: EVOLUTION AND INNOVATIONS (Ustozlar uchun, 2026)
The endoscopic endonasal approach (EEA) represents a paradigm shift in neurosurgery, transitioning from a "keyhole" microscopic view to a panoramic endoscopic visualization of the ventral skull base. This review synthesizes the historical evolution, anatomical principles, technological innovations, and clinical outcomes associated with EEA. We analyze the transition from the microscope to the endoscope, the development of modular skull base corridors, and the reconstructive techniques that have made expanded approaches viable.